STRATEGI PENCITRAAN ARIEF R WISMANSYAH DAN SACHRUDIN DALAM MENGHADAPI PEMILUKADA TAHUN 2018 - Mike Indarsih; Lili yana; Hani Yunaini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research aims to megetahui Imaging strategy conducted by the Campaign team of Arief and Sachrudin in the face of Pemilukada year 2018. The type of research used are descriptive, qualitative approach that gives an overview of the research object of empirical conditions based on the character. Peneitian method used is the method of case studies. The technique of data collection conducted in-depth interviews with with some of the speakers. The results of the research are Sachrudin and Arief Campaign Team managed to do the imaging strategy hook voters, Arief and Sachrudin wins hands down against a blank Box. by acquiring 85.80 percent and empty boxes grabbed 14.20 percent